Statin Therapy Alters Lipid Storage in Diabetic Skeletal Muscle - Rebalka, Irena A.; Raleigh, Matthew J.; Snook, Laelie A.; Rebalka, Alexandra N.; MacPherson, Rebecca E. K.; Wright, David C.; Schertzer, Jonathan D.; Hawke, Thomas J. (Frontiers in Endocrinology, 2016)
While statins significantly reduce cholesterol levels and thereby reduce the risk of cardiovascular disease, the development of myopathy with statin use is a significant clinical side-effect. Recent guidelines recommend increasing inclusion criteria for statin treatment in diabetic individuals; however, the impact of statins on skeletal muscle health in those with diabetes (who already suffer from impairments in muscle health) is ill-defined. Here we investigate the effects of Fluvastatin treatment on muscle health in wild-type and streptozotocin (STZ)-induced diabetic mice. Wild-type and STZ-diabetic mice received diet enriched with 600 mg/kg Fluvastatin or control chow for 24 days. Muscle morphology, intra and extracellular lipid levels, and lipid transporter content was investigated. Our findings indicate that short-term Fluvastatin administration induced a myopathy that was not exacerbated by the presence of STZ-induced diabetes. Fluvastatin significantly increased ectopic lipid deposition within the muscle of STZ-diabetic animals, findings that were not seen with diabetes or statin treatment alone. Consistent with this observation, only Fluvastatin-treated diabetic mice downregulated protein expression of lipid transporters FAT/CD36 and FABPpm in their skeletal muscle. No differences in FAT/CD36 or FABPpm mRNA content were observed. Altered lipid compartmentalization resultant of a downregulation in lipid transporter content in STZ-induced diabetic skeletal muscle was apparent in the current investigation. Given the association between ectopic lipid deposition in skeletal muscle and the development of insulin-resistance, our findings highlight the necessity for more thorough investigations into the impact of statins in humans with diabetes.